Clarithromycin Resistance Rates of Helicobacter pylori Infected Gastric Biopsies in Korea - Moo-Sang CHONG; Kyutaeg LEE (Korean Journal of Clinical Laboratory Science)
Gastric biopsies or tissue samples (4,698 samples) were collected from 50 local clinics or hospitals between January 2022 and December 2024 for the molecular detection of Helicobacter pylori and clarithromycin resistance using 23S ribosomal RNA genes. The clarithromycin resistance rates were analyzed. The patient’s age, sex, and regional distribution in Korea were investigated to determine the A2142G and A2143G mutations related to clarithromycin resistance. The clarithromycin resistance rate accounted for 32.6% of the 4,698 patients, with 40.5% and 25.7% in female and male, respectively. Among the mutation types, A2143G showed a higher frequency than A2142G in male and female. The resistance rate was higher in female than in male. In particular, the resistance rate in those showing the A2143G mutation in female increased every year. The mutation frequency was higher in female than in male. The A2143G mutation had a higher frequency than the A2142G mutation. In particular, the frequency of A2142G in female tended to increase yearly. The frequency showed differences according to age and region. Therefore, when treating H. pylori, the treatment outcome and the occurrence of resistance must be considered by referring to the clarithromycin resistance rate.